Ratu-Ratu Aceh Abad ke-17 M - Rd. Siti Sa'adah (Buletin Al-Turas, 2007)
The women government (power) in Aceh Darussalam Sultanate had happened for almost 60 years by four women sultanah from 1641-1699 AD. They are Sultanah Tajul Alam Safiatuddin Syah (1641- 1675). Sultanah Nurul Alam Nagiatuddin Syah (1675- 1678), Sultanah Inayat Zakiatuddin Syah (1678-1688), and Sultanah Kamalatuddin Syah (1689-1699). There are many factors caused the sultanah raising to the power in Aceh, some of them are the particular situation and condition, such as no prince crown born.